1995
DOI: 10.1007/bf00222121
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of powdery mildew resistance genes in common wheat (Triticum aestivum L.)

Abstract: — Major genes for resistance to the wheat powdery mildew pathogen, Erysiphe graminis f sp tritici, were analysed in 35 French wheat cultivars and in part in their parents. Cultivars were tested with a set of differential pathogen isolates which had specific interactions for each host line. The results were supplemented by cytological investigations and by consideration of pedigrees. Eighteen cultivars showed susceptible reactions. The remainder formed 9 groups with 1 or 2 resistance genes. Of the 5 known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…Therefore both the accuracy and efficiency for selection on the dominant homozygous genotypes of single dominant gene based on a single marker are obviously higher than when based on phenotypic performance, and a map distance of 5.0 cM or less is sufficient for markerassisted selection in breeding programmes (Hartl et al, 1995).…”
Section: Molecular Marker-assisted Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore both the accuracy and efficiency for selection on the dominant homozygous genotypes of single dominant gene based on a single marker are obviously higher than when based on phenotypic performance, and a map distance of 5.0 cM or less is sufficient for markerassisted selection in breeding programmes (Hartl et al, 1995).…”
Section: Molecular Marker-assisted Selectionmentioning
confidence: 99%
“…Results from QTL studies cannot be reimplemented through marker-assisted selection because of uncertainty about whether the QTLs identified are real, and whether the identified QTLs segregate in the breeding population (Spelman & Bovenhuis, 1998b). Marker-assisted selection of economically important traits conferred by single major genes has also been mentioned or generally discussed in many publications (Talbert, 1993 ;Williams et al, 1994 ;Feuillet et al, 1995 ;Hartl et al, 1995 ;McCouch et al, 1997 ;Sun et al, 1997 ;Hausner et al, 1999) and even conducted in tomato for the Tm-2 locus (Young & Tanksley, 1989) and for the nematode resistance gene Gro1 (Ballvora et al, 1995). Markers associated with stress responses have practical application in accelerating breeding programmes (marker-assisted selection) aimed at improving the barley crop by introgressing genes from selected wild genotypes (Forster et al, 1997).…”
mentioning
confidence: 99%
“…RFLP, RAPD and AFLP markers linked to wheat powdery mildew resistance genes Pm1 (Hartl et al 1995(Hartl et al , 1999Hu et al 1997), Pm2 (Ma et al 1994), Pm3 (Hartl et al 1993), Pm4 (Ma et al 1994), Pm6 (Tao et al 2000), Pm8 (Hsam et al 2000), Pm12 (Jia et al 1996), Pm13 (Donini et al 1995;Cenci et al 1999), Pm18 (Hartl et al 1993), Pm21 (Qi et al 1996), Pm24 (Huang et al 2000b), Pm25 (Shi et al 1998), Pm26 (Rong et al 2000), Pm27 (Järve et al 2000), Pm29 (Zeller et al 2002) and Pm30 (Liu et al 2002) have been identified. Microsatellites, also termed simple sequence repeats (SSRs) as a new type of genetic marker reveal a much higher polymorphism in wheat than any other marker system (Plaschke et al 1995;Huang et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore we need to search for new sources of genetic resistance to powdery mildew for cultivated wheat and the wild relatives of cultivated wheats. Molecular marker technology is widely used to fi nd markers linked to target genes (Hartl et al, 1995, Schachermayr et al, 1995, Hu et al, 2001). Molecular marker analysis in wheat appears to be particularly suited for identifying markers linked to the powdery mildew resistance gene (Devos and Gale, 1992;Wang et al, 2000) and has been used for marker-assisted selection and gene pyramiding in wheat resistance breeding (Liu et al, 1998;Myburg, et al, 1998;Hu et al, 2000;Liu and Liu, 2000).…”
mentioning
confidence: 99%